Energy, Economic and Environmental Multi-objective Optimization of a Novel Hybrid Solar-geothermal Power Generation Using Organic Rankine Cycle for Off-Grid Application with Energy Storage - A. Mokhtari; A. Haqiqati (Iranica Journal of Energy and Environment)
The use of thermodynamic cycles for power generation is very important. The use of renewable energy in thermodynamic cycles instead of a heat source causes these cycles to become popular from an environmental point of view. In this study, Organic Rankine cycle (ORC) is considered for power generation. Ground source at 100 °C and flat plate collectors (FPC) have been used to provide the required heat. Also, an off grid residential building with 408 residents has been considered to provide power. For energy storage, the hydrogen system including proton electrolyte membrane (PEM) electrolyzer and fuel cell has been used. This cycle is used to supply the demand of the building from an economic and environmental point of view, with variable decisions of collector area, flow rate and tank volume for multi-objective optimization. The generated energy is initially consumed in the building and the excess power is stored in the form of hydrogen to be used during power shortage hours. The results showed that the payback time of the studied cycle is 6.32 years and the levelized cost of electricity (LCOE) was 0.26 $.kWh-1. Also, from the environmental point of view, 583.3 tons of CO2 will be reduced throughout the year.